Environmental and Ecological Risks Posed by Sediment Heavy Metals in Reservoirs: A Preliminary Study from Northwest Türkiye - Murat Tekiner; Mehmet Parlak; Tülay Tunçay (Journal of Agricultural Sciences)
Reservoir sediments are an important component of aquatic ecosystems. Concentrations, sources, pollution and ecological risks of heavy metals pose serious risks on sustainable management of these ecosystems. This research focuses on heavy metal contents, physicochemical properties, environmental and ecological risks of sediments in four reservoirs (Ayvacık, Bayramdere, Bayramiç, and Umurbey) in Northwest Türkiye. Bayramiç reservoir had greater sediment Al, Cu, Fe, Mn concentrations, clay and silt contents than the other reservoirs (Ayvacık, Bayramdere, and Umurbey). In all four reservoirs, sediment heavy metals were generally of natural origin. Although sediment pollution index was identified as “considerable contamination” for Mn, such a case was not detected for the other heavy metals (Cd, Co, Cr, Cu, Fe, Ni, Pb, and Zn). An ecological risk assessment was made for reservoir sediments and a “low contamination” was detected.